2020
DOI: 10.5194/hess-24-4291-2020
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation for continuous global assessment of severe conditions over terrestrial surfaces

Abstract: Abstract. LDAS-Monde is a global offline land data assimilation system (LDAS) that jointly assimilates satellite-derived observations of surface soil moisture (SSM) and leaf area index (LAI) into the ISBA (Interaction between Soil Biosphere and Atmosphere) land surface model (LSM). This study demonstrates that LDAS-Monde is able to detect, monitor and forecast the impact of extreme weather on land surface states. Firstly, LDAS-Monde is run globally at 0.25∘ spatial resolution over 2010–2018. It is forced by th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 97 publications
1
26
0
Order By: Relevance
“…This experiment showed improvements in ET and gross primary production. Albergel et al (2020) has jointly assimilated SSM and LAI using the Simplified Extended Kalman Filter data assimilation technique to predict the impact of extreme events like heatwaves and droughts on land surface conditions over the globe. They have used LDAS-Monde as the land surface model and assimilated ASCAT soil water index (SWI) and LAIGEOV1 LAI observation data within that model.…”
Section: Introductionmentioning
confidence: 99%
“…This experiment showed improvements in ET and gross primary production. Albergel et al (2020) has jointly assimilated SSM and LAI using the Simplified Extended Kalman Filter data assimilation technique to predict the impact of extreme events like heatwaves and droughts on land surface conditions over the globe. They have used LDAS-Monde as the land surface model and assimilated ASCAT soil water index (SWI) and LAIGEOV1 LAI observation data within that model.…”
Section: Introductionmentioning
confidence: 99%
“…ISBA interfaces with an atmospheric and a hydrological model but simulates above-ground plant biomass and LAI with a simplistic plant growth model (ISBA-A-gs) [30]. In another recent work, Albergel et al [31] performed a joint assimilation of satellite-derived LAI and soil water index into the ISBA model to monitor the impact of extreme events (heat waves and droughts), using the Simplified Extended Kalman Filter. This work stems from the studies discussed above and further investigates the potential of jointly assimilating satellite LAI and soil moisture products.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for the first time, it jointly assimilates GLASS LAI and SMAP soil moisture within the Noah-MP model over the CONUS domain. Noah-MP uses a more sophisticated dynamic vegetation model scheme compared to other similar models used in the literature (e.g., ISBA) [31]. As past work showed that LAI assimilation alone could not improve the estimation of soil moisture (specifically surface soil moisture), the main goal of this work is to improve our estimation and understanding of soil moisture storages in addition to analyzing the impact on vegetation variables.…”
Section: Introductionmentioning
confidence: 99%
“…Recent extreme droughts in Europe have provided strong research foci in the hydrological community to better understand and forecast periods of water stress (Albergel et al., 2020; Bakke et al., 2020; Kleine et al., 2020; Smith et al., 2020a). In line with long‐term climate change projections, the extreme drought in 2018–2019 provided a unique opportunity to investigate expected regional climate change impacts both in terms of monitoring (e.g., the TERENO observatories in Germany [Heinrich et al., 2019; Wollschläger et al., 2016]) and modeling (e.g., Samaniego et al., 2018; Smith et al., 2020a) flux‐storage dynamics.…”
Section: Introductionmentioning
confidence: 99%